Livin' on the edge: the importance of adjacent intermittent habitats in maintaining macroinvertebrate diversity of permanent freshwater marsh systems. Issue 3 (3rd July 2018) - Boda, Pál; Móra, Arnold; Várbíró, Gábor; Csabai, Zoltán
ABSTRACT: Taxonomic and functional patterns of macroinvertebrate communities were investigated to reveal the importance of different habitat units within a marsh system in maintaining its macroinvertebrate diversity. Hydrogeomorphic units based on their functional characteristics were used to distinguish 3 types of aquatic habitats within the marsh system: (1) Core Unit (CU), a permanent inundation of a wetland in the central position of a marsh system; (2) Transitional Unit (TU), a seasonal to intermittent inundation of a wetland, with seasonal saturation; and (3) Satellite Unit (SU), seasonal depression wetlands with ephemeral to intermittent saturation. We hypothesized that communities in each Unit would have specific taxonomic and functional features. Species richness was highest in the TU, with unique community composition in the SU, and moderately high species richness characterized by a stable community with high taxonomic distinctness in the CU. The metacommunity of the entire marsh was nearly random with a substantial equilibrium between beta-diversity features: replacement and dissimilarity. Our results suggest that the combination of directly connected or isolated waterbodies in close proximity to a large core waterbody is likely to maintain the highest level of diversity. Each Unit has unique characteristics and provides habitats for species with different ecological traits; thus, different aquatic habitats of a marsh system should be considered together as one meaningful ecological entity.